2004
DOI: 10.1093/brain/awh098
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing and neural responses to pain among persons with fibromyalgia

Abstract: Pain catastrophizing, or characterizations of pain as awful, horrible and unbearable, is increasingly being recognized as an important factor in the experience of pain. The purpose of this investigation was to examine the association between catastrophizing, as measured by the Coping Strategies Questionnaire Catastrophizing Subscale, and brain responses to blunt pressure assessed by functional MRI among 29 subjects with fibromyalgia. Since catastrophizing has been suggested to augment pain perception through e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
518
6
22

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 779 publications
(578 citation statements)
references
References 42 publications
32
518
6
22
Order By: Relevance
“…The RC index of the FIQ physical impairment scale indicated responder rates of 58.1%, 38.1%, and 2.5% in the OBT, CBT, and AP groups, respectively ( 2 [2] ϭ 14.95, P Ͻ 0.005). The percentage of CBT and OBT responders was significantly higher than that of the AP responders (CBT versus AP: 2 [1] ϭ 7.23, P Ͻ 0.05; OBT versus AP: 2 [1] ϭ 14.02, P Ͻ 0.001). CBT and OBT responders were not significantly different (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The RC index of the FIQ physical impairment scale indicated responder rates of 58.1%, 38.1%, and 2.5% in the OBT, CBT, and AP groups, respectively ( 2 [2] ϭ 14.95, P Ͻ 0.005). The percentage of CBT and OBT responders was significantly higher than that of the AP responders (CBT versus AP: 2 [1] ϭ 7.23, P Ͻ 0.05; OBT versus AP: 2 [1] ϭ 14.02, P Ͻ 0.001). CBT and OBT responders were not significantly different (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of pain ( 2 [ Canonical discriminant analyses found that pain behavior discriminated the CBT group from the OBT and AP groups (Wilks' [2] ϭ 0.488, P Ͻ 0.001; F[2] ϭ 11.561, P Ͻ 0.001). CBT patients responding with clinically significant reduction of physical impairment showed lower pain behaviors prior to the treatment in contrast to OBT responders who showed a greater number of pain behaviors and AP patients who displayed extremely high pain behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain catastrophizing is suggested to increase pain sensitivity through enhanced attention to painful stimuli as well as heightened emotional responses to pain. Indeed, catastrophizing has been associated with increased activity in brain areas related to anticipation of pain, attention to pain, and emotional aspects of pain and motor control 21,38 . Those who catastrophize about pain preferentially process pain-related information and interpret even ambiguous sensations as painful 41 .…”
Section: Discussionmentioning
confidence: 99%